Analysing the importance of sustainability‐oriented service quality in competition environment - Ozbekler, Turkan Muge; Ozturkoglu, Yucel (Business strategy and the environment, 2020)
The logistics sector is one of the most important domains in the service sector in understanding the increasing scale of business activities along with globalization. Due to the nature of the service sector, where competition is increasingly concentrated, the main objective of firms is the creation of their strategy on competitive advantage in regard with knowing the level of quality of the services offered and the firm's image from the customers' point of view. Trying to adapt to the changing conditions of the market drives firms to integrate their competing areas into their sustainability dimensions (economic, social, and environmental) with the aim of increasing their perceived quality through differentiating their business to achieve a sustainable competitive advantage. The aim of this study is to examine the quality level perceived by logistics service providers in terms of triple bottom line approach and to determine the relationship between them for sustainable competition. In line with exploratory methods, factor analysis was used with the aim of finding out a new scale to the literature about the examination of the relationship between quality perception and corporate sustainability in the frame of competition. In this context, data of 120 logistics service providers were collected and analysed. According to the results, the content of the subject consists of nine factors and 29 interrelated subdimensions. As a result of the research, firms have emphasized on the importance of reaching the competition by expanding their quality perceptions within the scope of corporate sustainability in parallel with the increasing customer demands and expectations.